Effectiveness of reactive oral cholera vaccination in rural Haiti: a case-control study and bias-indicator analysis. Issue 3 (March 2015) - Ivers, Louise C; Hilaire, Isabelle J; Teng, Jessica E; Almazor, Charles P; Jerome, J Gregory; Ternier, Ralph; Boncy, Jacques; Buteau, Josiane; Murray, Megan B; Harris, Jason B; Franke, Molly F
Summary: Background: Between April and June, 2012, a reactive cholera vaccination campaign was done in Haiti with an oral inactivated bivalent whole-cell vaccine. We aimed to assess the effectiveness of the vaccine in a case-control study and to assess the likelihood of bias in that study in a bias-indicator study. Methods: Residents of Bocozel or Grand Saline who were eligible for the vaccination campaign (ie, age ≥12 months, not pregnant, and living in the region at the time of the vaccine campaign) were included. In the primary case-control study, cases had acute watery diarrhoea, sought treatment at one of three participating cholera treatment units, and had a stool sample positive for cholera by culture. For each case, four control individuals who did not seek treatment for acute watery diarrhoea were matched by location of residence, enrolment time (within 2 weeks of the case), and age (1–4 years, 5–15 years, and >15 years). Cases in the bias-indicator study were individuals with acute watery diarrhoea with a negative stool sample for cholera. Controls were selected in the same manner as in the primary case-control study. Trained staff used standard laboratory procedures to do rapid tests and stool cultures from study cases. Participants were interviewed to collect data on sociodemographic characteristics, risk factors for cholera, and self-reported vaccination. Data were analysed by conditional logistic regression, adjusting for matching factors. Findings: From Oct 24, 2012, to March 9, 2014, 114 eligible individuals presented with acute watery diarrhoea and were enrolled, 25 of whom were subsequently excluded. 47 participants were analysed as cases in the vaccine effectiveness case-control study and 42 as cases in the bias-indicator study. 33 (70%) of 47 cholera cases self-reported vaccination versus 167 (89%) of 188 controls (vaccine effectiveness 63%, 95% CI 8–85). 27 (57%) of 47 cases had certified vaccination versus 147 (78%) of 188 controls (vaccine effectiveness 58%, 13–80). Neither self-reported nor verified vaccination was significantly associated with non-cholera diarrhoea (vaccine effectiveness 18%, 95% CI −208 to 78 by self-report and −21%, −238 to 57 by verified vaccination). Interpretation: Bivalent whole-cell oral cholera vaccine effectively protected against cholera in Haiti from 4 months to 24 months after vaccination. Vaccination is an important component of efforts to control cholera epidemics. Funding: National Institutes of Health, Delivering Oral Vaccines Effectively project, and Department of Global Health and Social Medicine at Harvard Medical School .